TRANSFORMATIONS OF TRADITIONAL AND MODERN RETAIL TRADE IN THE FOOD MARKET OF UZBEKISTAN (Marketing Journal, 2026)
This article analyzes the structural transformation of food retail and value chains on both global and national scales. It reveals the profound changes occurring in food production, processing, distribution, and consumption systems in the context of accele rating urbanization, rising household incomes, increasing female employment, technological advancements, and globalization. The article illuminates the formation and developmental stages of supermarkets and the dynamics of their share in global food retail based on statistical data. Additionally, it analyzes transformations in the e - commerce and food service sectors. The study evaluates the level of urbanization, growth of real incomes, and changes in the structure of food retail trade in Uzbekistan through various indicators. The results demonstrate the parallel development of traditional and modern forms of trade in Uzbekistan, substantiating the significance of these processes for food security, consumer well -being, and state policy.
Keywords: food retail; value chains; supermarkets; urbanization; consumer habits; logistics; e -commerce; food security; Uzbekistan agri -food market; trade transformation. № 1 -SON YANVA R; 202 6-YIL 251